Investigating the factors contributing to an excessive number of students in primary schools using GIS technology: A case study of Zanzibar’s Urban West Region - Jecha, Mzee Kheir; Haji, Haji A.; Kombo, Omar Haji (Journal of Education For Sustainable Innovation, 2024)
ICT, or Information and Communication Technology, is a versatile technology that is used in various fields. In this context, the researcher delved into GIS and School Mapping. School mapping is the process of accurately locating schools on a map of a particular area. To achieve this, a GPS receiver is used to capture precise coordinates of each school location, which are then used to create a map. The schools themselves are treated as spatial data, meaning that they are referenced to specific locations on the earth. Spatial data typically includes information about the location and shape of features on a map, while attribute data provides additional details about those features. For example, the location of schools would be spatial data, while attribute data might include the name of the school, the level of education taught, and the school's capacity. This research aims to investigate the factors contributing to an increase in the number of students in schools using GIS technology in the urban west region of Zanzibar. The results of this investigation could help better understand the sources and impact of changes in the student population, as well as provide important information to policymakers and education planners looking forward to improve the education system.